High Calorie Diet with a Combination of Intermittent Restriction Affects the Reproductive Cycle and The Uterine Weight of Mice (Mus Musculus) - Kumalasari, Anggraeni Dyah; Herawati, Lilik; Argarini, Raden; Lukitasari, Lina; Othman, Zulhabri; Ningrum, Astika Gita (Folia Medica Indonesiana, 2021)
Highlight: • High-calorie diet influence with interval restrictions combination on the reproductive cycle and weight of the uterus in mice were analyzed. • Calories balance impact for female reproductive health. Abstract : Balanced calories affected for body health and daily activities. Lose of energy can disturb the health and daily activities, while over calorie for diets also causes disorders such as metabolic. When there are excess calories in the body will be involved. It can be an obesity risk, diabetes mellitus, fertility disorder, cancer, and cardiovascular disease. Furthermore, in women there can be an increase in menstrual disorders and fertility disorder risk (Silvestris et al., 2018). This study aims to analyze highcalorie diet influence with interval restrictions combination on the reproductive cycle and weight of the uterus in mice. Experimental laboratory is a mouse (mus musculus) female's balb/c as object population. Sampling techniques using probability sampling with simple random sampling type. The study results on fisher's exact test gave a result of p > 0.05 so there was no significant difference between control group, high calorie diet group, and high calorie diet with interval restrictions group on the results of vaginal swabs /post-treatment reproductive cycle. The study outcome on robust tests between control, high calorie diet, and high calorie diet with interval restrictions groups. Obtained results (p < 0.05) that mean there are some significant discrepancies in the weight of uterine organ between groups. Calories balance in the body can impact female reproductive health.